Evidence, Ethics & Social Policy Dilemmas - Steven I. Miller; L. Arthur Safer (Arizona State University, 1993)
Within the philosophy of the social sciences, the relationship between evidence, ethics, and social policy is in need of further analysis. The present paper is an attempt to argue that while important social policies can, and perhaps ought to be, grounded in ethical theory, they are seldom articulated in this fashion due to the ambiguity surrounding the "evidence condition." Using a consequentialist-utilitarian framework, and a case study of a policy dilemma, the authors analyze the difficulties associated with resolving policy-based dilemmas which must appeal to evidential support as a justification for an ethical stand. Implication for the relevance of ethics to social policy formulation are discussed in detail.